User preferences for ui design elements: impact on learning and skill development on coursera, edx, and stepik - Ospankhan, A.; Kalpeyeva, Z. (Харківський національний автомобільно-дорожній універститет, 2024)
With the development of digital technologies and the proliferation of digital applications and platforms, the issue of educating users and developing their skills in using these technologies is becoming increasingly important. One of the key challenges is ineffective or unsatisfactory user interface design, which can impede learning and hinder the development of user skills.The purpose of this study is to analyze the impact of UI design on user learning and skill development in digital applications and platforms. The study aims to identify methods and strategies that optimize UI design to improve learning and skill development. To achieve this objective, an extensive literature review is conducted, analyzing existing research practices in the area of user interface design and its impact on learning. In addition, empirical data is collected and analyzed through user testing and surveys to identify practical recommendations and best practices.
Keywords: ui design; ux; user learning; digital applications; education and technology; visual components of the learning platform (VCLP).